Autorzy:Ewa Duvnjak, Ewa Kokiernak-Jurkiewicz, Maria Wójcicka
Wydawnictwo:WSiP
Rok wydania:2015
Wykonaj odejmowanie a) (6a² +2a+1)-(-3a²-2a+5)4.09 gwiazdek na podstawie 11 opinii

Wykonaj odejmowanie a) (6a² +2a+1)-(-3a²-2a+5)

4Zadanie
5Zadanie
6Zadanie
7Zadanie
8Zadanie

a) `(6a^2+2a+1)-(-3a^2-2a+5)=6a^2+2a+1+3a^2+2a-5=9a^2+4a-4`

b) `(12 1/2m^2-1 1/4n^2-1,6)-(2 1/4m^2+3 3/4n^2+2,4)=` `12 1/2m^2-1 1/4n^2-1,6-2 1/4m^2-3 3/4n^2-2,4=` `12 2/4m^2-2 1/4m^2-5n^2-4=10 1/4m^2-5n^2-4`

c) `(1,5x^2y-3/4x^2-15)-(2/5x^2y-2 2/3-1/8x^2)=``1,5x^2y-3/4x^2-15-2/5x^2y+2 2/3+1/8x^2=` `1,5x^2y-0,4x^2y-6/8x^2+1/8x^2-12 1/3=1,1x^2y-5/8x^2-12 1/3`